Identification Of Peat Soil Thickness Using The Geolectrical Resistivity Method (Case Study: Parit Demang Dalam Road, Pontianak City) - Bella Ankara Can; Zulfian Zulfian; Joko Sampurno (Departement of Physics Faculty of Mathematics and Natural Sciences, and Institute of Research and Community Services Udayana University, Kampus Bukit Jimbaran Badung Bali, 2026)
Parit Demang is an area with peatland used for residential purposes, so information on soil thickness in this area is very important for development planning. This study aims to identify peat soil thickness using the Wenner-Schlumberger configuration of the geoelectric method. Data was obtained through three measurement lines, each 50 m long. The 2D inversion modeling at the study site showed that the resistivity values of the peat layer ranged from 32.4 to 315 Ωm, with peat soil thickness between 2.3 to 5.5 m. The interpretation results were validated with soil sample drilling data. The layer located under the peat soil was identified as clay with resistivity between 1.56 to 15.2 Ωm. Information on peat soil thickness can be used as a basis for selecting soil improvement methods by the local community and related parties for development planning, particularly in the process of house construction.